To Study the Effect of the Amount of Dispersed Fibers on the Cement Stone and Determine the Optimal Composition - Ibragimov Navruzbek Shaydullayevich (International Journal on Orange Technologies, 2021)
The article presents the results of experimental research on the effect of the amount of basalt fiber on the physical and mechanical properties of fine-grained concrete. The selected composition of micro-reinforced sandy concrete is recommended for the manufacture of thin-walled spatial structures. Conclusions on the research work carried out are presented.